De novo putative loss‐of‐function variants in TAF4 are associated with a neuro‐developmental disorder. Issue 12 (10th August 2022) - Janssen, Beau D. E.; van den Boogaard, Marie‐Jose H.; Lichtenbelt, Klaske; Seaby, Eleanor G.; Stals, Karen; Ellard, Sian; Newbury‐Ecob, Ruth; Dixit, Abhijit; Roht, Laura; Pajusalu, Sander; Õunap, Katrin; Firth, Helen V.; et al.
Abstract: TATA‐binding protein associated factor 4 (TAF4) is a subunit of the Transcription Factor IID (TFIID) complex, a central player in transcription initiation. Other members of this multimeric complex have been implicated previously as monogenic disease genes in human developmental disorders. TAF4 has not been described to date as a monogenic disease gene. We here present a cohort of eight individuals, each carrying de novo putative loss‐of‐function (pLoF) variants in TAF4 and expressing phenotypes consistent with a neuro‐developmental disorder (NDD). Common features include intellectual disability, abnormal behavior, and facial dysmorphisms. We propose TAF4 as a novel dominant disease gene for NDD, and coin this novel disorder "TAF4‐related NDD" (T4NDD). We place T4NDD in the context of other disorders related to TFIID subunits, revealing shared features of T4NDD with other TAF‐opathies.